Globalization and Turkey's energy policies - Kıvılcım, Fulya (My University, 2014)
Along with the concept of globalization, the changing paradigm in international politics has been attached to energy policies of states. From an economic perspective to political tendencies, the interdependency of energy and security concerns illustrates the possible outbreak of wars and national conflicts around the globe. Turkey, within the geo-political and geo-strategic position, is under a competitive challenge of security paradigm whilst the hegemonic powers' energy policies attach to her hinterland in the region. This chapter examines the energy policies of great powers in the international arena and the effects of these policies on developing countries. In this study, alternative security strategies and energy policies have been assessed for long-term economic and politic stability for Turkey.